Interstitial duplication of the short arm of chromosome 2: report of a new case and review. Issue 9 (September 1997) - Mégarbané, A; Souraty, N; Prieur, M; Theophile, D; Chédid, P; Augé, J; Vekemans, M
Abstract : An 18 month old girl was referred to us because of dysmorphic features and psychomotor and growth retardation. On physical examination, she was found to have microcephaly, open fontanelles, a prominent forehead, a flat occiput, hypertelorism, sparse eyebrows, a small nose with a depressed nasal bridge, a bulging philtrum, a thin upper lip, a high arched palate, low set and posteriorly rotated ears, a small mandible, a short neck with a low hair line, and eye malformations. High resolution chromosome analysis identified a de novo direct duplication of the 2p21.00–>p24.2 region. The phenotype of de novo partial trisomy 2p is discussed.